The rise and fall of us manufacturing: Re-examination of long-run spatial trends - Nicholas Crafts; Alexander Klein (University of Kent, School of Economics, 2019)
We re-examine the long-run geographical development of U.S. manufacturing industries using recent advances in spatial concentration measures. We construct spatially-weighted indices of the geographical concentration of U.S. manufacturing industries during the period 1880 to 1997 using data from the Census of Manufactures and Bureau of Labor Statistics. Doing so we improve upon the existing indices by taking into account industrial structure and checkerboard problem. Several important new results emerge. First, we find that average spatial concentration was much lower in the late 20th- than in the late 19th-century and that this was the outcome of a continuing reduction over time. Second, spatial concentration of industries did not increase in early twentieth century as shown by traditional indices but rather declined, implying that we do not find an inverted-U shape pattern of long-run spatial concentration. Third, the persistent tendency to greater spatial dispersion was characteristic of most manufacturing industries. Fourth, even so, economically and statistically significant spatial concentration was pervasive throughout this period.
Keywords: N62; N92; R12; 330; manufacturing belt; spatial concentration; transport costs